(untitled) (LACCEI, 2024)
The present investigation was carried out at the Kuntur Wassi archaeological site, located in the Kuntur Wassi Population Center, San Pablo province, Cajamarca department - Peru. The work was based on the application of the technique of recording species by direct detection. This technique must be understood as a limited or standardized evaluation based on search time In the elaboration of an inventory of flora and fauna, it was considered to recognize the different species present in the area, for the identification of the flora species it is necessary to take into account the existing plant formations and also to inventory the already recognized species, it is necessary to It took into account making a vegetation map in order to work with the topographic base, to proceed to carry out the field work where the species are identified in the field and a herbarium was carried out that intervened in the identification In order to recognize the fauna species, data was collected from private observers and all the information available in the area and finally the field work was carried out, directly collecting the data on the land involved. The instruments to collect information on flora species are the use of base information, mapping of detailed units, size of the sample unit, shape or distribution of sample units, and species description sheets.